Vaping habits and respiratory symptoms using a smartphone app platform. - Lee, Mi-Sun S; Eum, Ki-Do.; Allen, Joseph G; Onnela, Jukka-Pekka.; Christiani, David C (Tufts University. Tisch Library., 2024)
Keywords: E-cigarettes, Vaping, Repeated measures, Epidemiology, Respiratory health, App platforms, Electronic nicotine delivery devices.; Springer Open.